HUBUNGAN AKTIVITAS FISIK DAN POLA MAKAN TERHADAP KADAR GULA DARAH PASIEN DIABETES MELITUS - Ischak, Netty Ino; Handayani, Sekar; Rofiqoh, Rofiqoh; Mu'awanah, Mu'awanah; Widhi, Anisa Sekar (Ensiklopedia of Journal, 2024)
Diabetes mellitus is a metabolic disease characterized by hyperglycemia. Hyperglycemia is a medical condition where there is an increase in blood glucose levels that exceed normal limits. Unhealthy diet and lack of physical activity are one of the causes of uncontrolled blood sugar levels. This study aims to determine the relationship of physical activity and diet to blood sugar levels of patients with diabetes mellitus in the Internal Medicine Polyclinic of Selasih Regional General Hospital, Pelalawan Regency. Research is quantitative with a cross sectional approach. The total sample of 84 respondents was taken using accidental sampling technique. Data analysis was performed univariate and bivariate with chi square test. The results showed that the majority of low physical activity were 49 respondents (58.3%), poor diet were 59 respondents (70.2%) and uncontrolled blood sugar levels were 64 respondents (76.2%). There is a relationship between physical activity (0.030) and diet (0.011) on blood sugar levels of diabetes mellitus patients at the Internal Medicine Polyclinic of Selasih Regional General Hospital, Pelalawan Regency. It is recommended to respondents to be able to do physical activities such as and adjust their diet so that the respondent's blood sugar levels are controlled and prevent worse conditions due to complications.Keywords: Diabetes mellitus, blood sugar, physical activity, diet